PPARs in Alzheimer's Disease - Kummer, Markus P. (Hindawi Publishing Corporation, 2008)
Peroxisome proliferator-activated receptors (PPARs) are well studied for their peripheral physiological and pathological impact, but they also play an important role for the pathogenesis of various disorders of the central nervous system (CNS) like multiple sclerosis, amyotrophic lateral sclerosis, Alzheimer's, and Parkinson's disease. The observation that PPARs are able to suppress the inflammatory response in peripheral macrophages and in several models of human autoimmune diseases lead to the idea that PPARs might be beneficial for CNS disorders possessing an inflammatory component. The neuroinflammatory response during the course of Alzheimer's disease (AD) is triggered by the neurodegeneration and the deposition of the β-amyloid peptide in extracellular plaques. Nonsteroidal anti-inflammatory drugs (NSAIDs) have been considered to delay the onset and reduce the risk to develop Alzheimer's disease, while they also directly activate PPARγ. This led to the hypothesis that NSAID protection in AD may be partly mediated by PPARγ. Several lines of evidence have supported this hypothesis, using AD-related transgenic cellular and animal models. Stimulation of PPARγ receptors by synthetic agonist (thiazolidinediones) inducing anti-inflammatory, anti-amyloidogenic, and insulin sensitising effects may account for the observed effects. Several clinical trials already revealed promising results using PPAR agonists, therefore PPARs represent an attractive therapeutic target for the treatment of AD.